High-Yield-Related Genes Participate in Mushroom Production - Wang, Fang; Li, Fengzhu; Han, Luyang; Wang, Jingzi; Ding, Xupo; Liu, Qinhong; Jiang, Mingguo; Li, Hailin (Journal of fungi (Basel), 2024)
In recent years, the increasing global demand for mushrooms has made the enhancement of mushroom yield a focal point of research. Currently, the primary methods for developing high-yield mushroom varieties include mutation- and hybridization-based breeding. However, due to the long breeding cycles and low predictability associated with these approaches, they no longer meet the demands for high-yield and high-quality varieties in the expansive mushroom market. Modern molecular biology technologies such as RNA interference (RNAi) and gene editing, including via CRISPR-Cas9, can be used to precisely modify target genes, providing a new solution for mushroom breeding. The high-yield genes of mushrooms can be divided into four categories based on existing research results: the genes controlling mycelial growth are very suitable for genetic modification; the genes controlling primordium formation are directly or indirectly regulated by the genes controlling mycelial growth; the genes controlling button germination are more difficult to modify; and the genes controlling fruiting body development can be regulated during the mycelial stage. This article reviews the current research status for the four major categories of high-yield-related genes across the different stages of mushroom growth stages, providing a foundation and scientific basis for using molecular biology to improve mushroom yield and promote the economic development of the global edible-mushroom industry.